Methodology of analysis of the enterprise’s financial condition - Chubai, Volodymyr (Видавництво Львівської політехніки, 2013)
The aspects the observance of that will give an opportunity to provide high reliability of results of financial condition analysis are singled, methodology of it realization is improved in the article. In particular, stages of financial condition analysis of the enterprise taking into account the impact of its internal and external environment are proposed.
Keywords: financial analysis; financial condition; enterprise